Evaluasi Program Jakarta Recycle Centre (Jrc) Di Kecamatan Pesanggrahan Jakarta Selatan - Abiyyah, Maryam; Riswanda, Riswanda (Universitas Muhammadiyah Mataram, 2026)
The issue of waste management in the Province of DKI Jakarta remains a major concern due to the increasing volume of household waste and the limited capacity of the Bantargebang Integrated Waste Management Facility (TPST), which has experienced overcapacity. As an effort to address this problem, the Provincial Government of DKI Jakarta through the Integrated Waste Management Unit (UPST) of the Environmental Agency launched the Jakarta Recycle Centre (JRC) Program based on Governor Regulation No. 77 of 2020 concerning Waste Management at the Neighborhood Association (RW) Level. This program, developed in collaboration with the Osaki City Government of Japan, focuses on community-based waste management through the application of the Reduce, Reuse, Recycle (3R) principles. It aims to increase public participation in reducing the volume of waste transported to TPST Bantargebang. This study aims to evaluate the JRC program using a descriptive qualitative method. Data were collected through observation, interviews, and document studies, then analyzed using the Miles, Huberman, & Saldana model. The evaluation employed the CIPP (Context, Input, Process, Product) model developed by Stufflebeam. The findings indicate that the implementation of the program has not been fully optimal and still requires improvement in the future, including increasing community participation, infrastructure, human resources for implementers, fluctuations in the price of recycled materials, difficulties for offtakers, as well as technical challenges in the field such as transportation time, weak coordination, and lack of transparency of results.